Conformal isoparametric spacelike hypersurfaces in conformal spaces Q⁴₁ and Q⁵₁ - Bianping Su; Shichang Shu (Український математичний журнал, 2012)
We study the conformal geometry of conformal spacelike hypersurfaces in the conformal spaces Q⁴₁ and Q⁵₁. We obtain a complete classification of conformal isoparametric spacelike hypersurfaces in Q⁴₁ and Q⁵₁.